2012
DOI: 10.1175/jpo-d-11-039.1
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of Barotropic and Baroclinic Tides in the Monterey Bay Area

Abstract: A detailed energy analysis of the barotropic and baroclinic M2 tides in the Monterey Bay area is performed. The authors first derive a theoretical framework for analyzing internal tide energetics based on the complete form of the barotropic and baroclinic energy equations, which include the full nonlinear and nonhydrostatic energy flux contributions as well as an improved evaluation of the available potential energy. This approach is implemented in the Stanford Unstructured Nonhydrostatic Terrain-Following Ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
193
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(201 citation statements)
references
References 54 publications
(92 reference statements)
7
193
1
Order By: Relevance
“…Negative conversion rates seen in Fig. 6 are typical of numerical studies on internal tide energetics (Simmons et al, 2004;Kang and Fringer, 2012). A negative conversion occurs when energy is transferred from baroclinic tide to the barotropic tide and indicates interaction between locally and remotely generated baro- can be observed on the western part of the plateau around 82 • N, and also along the shelf break north of Spitsbergen.…”
Section: Fer Et Al: Tidal Mixing Near the Yermak Plateaumentioning
confidence: 68%
See 2 more Smart Citations
“…Negative conversion rates seen in Fig. 6 are typical of numerical studies on internal tide energetics (Simmons et al, 2004;Kang and Fringer, 2012). A negative conversion occurs when energy is transferred from baroclinic tide to the barotropic tide and indicates interaction between locally and remotely generated baro- can be observed on the western part of the plateau around 82 • N, and also along the shelf break north of Spitsbergen.…”
Section: Fer Et Al: Tidal Mixing Near the Yermak Plateaumentioning
confidence: 68%
“…The simulated tidal energy flux and conversion of barotropicto-baroclinic tidal energy are computed from the model by using the derivations presented in Kang and Fringer (2012). The vertically integrated, barotropic-to-baroclinic tidal energy conversion rates are obtained from…”
Section: Tidal Energy Conversion and Baroclinic Energy Fluxes From Stmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the largest submarine canyon along the west coast of the United States and has been the focus of several internal tide observational programs (Key, 1999;Kunze et al, 2002;Johnston et al, 2011;Kunze et al, 2012) and numerical modelling studies (Petruncio et al, 2002;Jachec et al, 2006;Wang et al, 2009;Kang and Fringer, 2012). In stratified seas, barotropic (surface) tidal flow across the sloping topography typical of submarine canyons can generate internal tides (internal gravity waves with tidal frequencies) by vertically displacing density surfaces (Bell, 1975;Baines, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical modelling studies of internal tides in the MSC region (Jachec et al, 2006;Carter, 2010;Hall and Carter, 2011;Kang and Fringer, 2012) have shown that the internal tide observed in the canyon is likely generated on Sur Slope, roughly 40 km to the south of the canyon mouth. Hall and Carter (2011) presented evidence that more remote generation sites in the region, including two offshore seamounts, have only a minor influence on the internal tide in the canyon.…”
Section: Introductionmentioning
confidence: 99%